2013
DOI: 10.1136/bmjopen-2013-003013
|View full text |Cite
|
Sign up to set email alerts
|

‘Have you seen what is on Facebook?’ The use of social networking software by healthcare professions students

Abstract: ObjectiveThe use of social networking software has become ubiquitous in our society. The aim of this study was to explore the attitudes and experiences of healthcare professional students using Facebook at our school, to determine if there is a need for development of policy to assist students in this area.DesignA mixed-methods approach was employed, using semistructured interviews to identify themes which were explored using an online survey. A combination of descriptive statistics and thematic analysis was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
76
0
8

Year Published

2016
2016
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 33 publications
10
76
0
8
Order By: Relevance
“…37 Other students consider their social media as a private activity and do not think it appropriate for their social media habits to be discussed or taught as part of their professional education. 38 Another study found that there was a noted 'disconnect between voiced concerns and a lack of any directed action to secure privacy' on Facebook. This was due to their opinion that it was 'tedious' to change/monitor privacy settings, because they self-reported that they didn't have anything unprofessional on their Facebook page, or that they didn't know how to change the privacy settings.…”
Section: Discussionmentioning
confidence: 99%
“…37 Other students consider their social media as a private activity and do not think it appropriate for their social media habits to be discussed or taught as part of their professional education. 38 Another study found that there was a noted 'disconnect between voiced concerns and a lack of any directed action to secure privacy' on Facebook. This was due to their opinion that it was 'tedious' to change/monitor privacy settings, because they self-reported that they didn't have anything unprofessional on their Facebook page, or that they didn't know how to change the privacy settings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of sophisticated and automatic tools for collecting and monitoring personal data and behavior has become increasingly common and less detectable. Studies have suggested that unprofessional uses of SM are frequent among health professionals and various improper behaviors, such as violations of patient privacy, posting sexually suggestive photos, defamation and criticism of others, and racist content online are among the most common problems detected on these platforms [17,[20][21][22][23][24][25].…”
Section: Ethical and Legal Considerations When Using Social Media Formentioning
confidence: 99%
“…O uso das mídias sociais com objetivos de aprendizagem cresce cada vez mais 3,4 , ao mesmo tempo em que a facilidade de viralização, ou seja,…”
unclassified